The Powers of the Court in terms of Section 7(2) of the Domestic Violence Act 116 of 1998: KS v AM 2018 (1) SACR 240 (GJ) - Moffat Maitele Ndou (Obiter, 2019)
The preamble of the Domestic Violence Act (116 of 1998) (DVA) recognises that domestic violence is a serious social evil and that there are high incidences of domestic violence in South Africa. The preamble further recognises that:a) victims of domestic violence are among the most vulnerable members of society;b) domestic violence takes many forms and may be committed in a wide range of domestic relationships; andc) the remedies previously available to victims of domestic violence have proved to be ineffective.The Constitution of the Republic of South Africa, 1996 (the Constitution) provides various rights that are also applicable to victims of domestic violence. The Constitution guarantees the right to dignity and to freedom and security of the person (see ss 10 and 12 of the Constitution respectively). Domestic violence against any person is a violation of these rights. The DVA further recognises that South Africa has international commitments to end violence against women and children in terms of the United Nations Convention on the Elimination of all Forms of Discrimination against Women and the Convention on the Rights of the Child. A right not to be subjected to domestic violence may not be specifically mentioned in international human rights law instruments, but freedom from all kinds of violence and the right to equality and human dignity is generally emphasised.The purpose of the DVA is to provide a legal remedy in the form of an interdict that prohibits a person from violating the rights of the complainant. In order to give effect to this purpose, section 7(1) of the DVA provides that the court may grant a protection order to protect the rights of the complainant. Section 7(2) of the DVA further grants the court the power to impose any additional conditions that it deems reasonably necessary to protect and provide for the safety, health or well-being of the complainant.In KS v AM (2018 (1) SACR 240 (GJ)), the court found that section 7(2) of the DVA empowered the court to order the seizure of the respondent’s digital equipment to remove any photograph, video, audio and/or records relating to the complainant. This case note examines the decision in KS v AM (supra) and determines whether the decision is justifiable in law. The definition of domestic violence is discussed first and thereafter the remedies available in terms of the DVA are examined. A discussion of the judgment in KS v AM (supra) follows.